2020
DOI: 10.1016/j.ijpam.2019.12.001
|View full text |Cite|
|
Sign up to set email alerts
|

Pda

Abstract: Management of persistent patent ductus arteriosus (PDA) continues to be a challenging issue. The attitude toward PDA has shifted in the opposite direction during the last 20 years, from advocating an aggressive and early closure toward a call for watchful observation. While persistent PDA may cause challenges in the medical management of preterm neonates secondary to volume overload, pulmonary edema or hemorrhage, hypotension, and impaired tissue perfusion, its contribution toward long-term neonatal morbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…This research, as well as our study, found that PDA was signi cantly correlated with ROP in the multivariate logistic regression analysis adjusted for GA and BW [34]. Taking these results into account, it is possible to hypothesize that hs-PDA, in critical ill newborns, may increase the risk of ROP due to hemodynamic instability that, in turn, may in uence development of the immature and incompletely vascularized retina [35]. We did not observe the association between hs-PDA and ROP in ELGAN and ELBW patients.…”
Section: Discussionsupporting
confidence: 68%
“…This research, as well as our study, found that PDA was signi cantly correlated with ROP in the multivariate logistic regression analysis adjusted for GA and BW [34]. Taking these results into account, it is possible to hypothesize that hs-PDA, in critical ill newborns, may increase the risk of ROP due to hemodynamic instability that, in turn, may in uence development of the immature and incompletely vascularized retina [35]. We did not observe the association between hs-PDA and ROP in ELGAN and ELBW patients.…”
Section: Discussionsupporting
confidence: 68%
“…It is known that pO 2 regulates the production of predominant regulators of retinal angiogenesis, therefore O 2 therapy could be responsible for the retinal damage associated with ROP pathogenesis [35]. However, taking these results into account, it is possible to hypothesize that hs-PDA, in critical ill newborns, may contribute to increase the risk of ROP due to hemodynamic instability that, in turn, may influence development of the immature and incompletely vascularized retina [36]. We did not observe the association between hs-PDA and ROP in ELGAN and ELBW patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that pO 2 regulates the production of predominant regulators of retinal angiogenesis, therefore O 2 therapy could be responsible for the retinal damage associated with ROP pathogenesis [36]. However, taking these results into account, it is possible to hypothesize that hs-PDA, in critical ill newborns, may contribute to increase the risk of ROP due to hemodynamic instability that, in turn, may in uence development of the immature and incompletely vascularized retina [37]. We did not observe the association between hs-PDA and ROP in ELGAN and ELBW patients.…”
Section: Discussionmentioning
confidence: 99%